GO-DACT: a phase 3b randomised, double-blind, placebo-controlled trial of GOlimumab plus methotrexate (MTX) versus placebo plus MTX in improving DACTylitis in MTX-naive patients with psoriatic arthritis. Issue 4 (19th March 2020) - Vieira-Sousa, Elsa; Alves, Pedro; Rodrigues, Ana M; Teixeira, Filipa; Tavares-Costa, Jose; Bernardo, Alexandra; Pimenta, Sofia; Pimentel-Santos, Fernando M; Gomes, João Lagoas; Aguiar, Renata; Pinto, Patrícia; Videira, Taciana; et al.
Abstract : Objectives: To assess the efficacy of golimumab in combination with methotrexate (MTX) versus MTX monotherapy in psoriatic arthritis (PsA) dactylitis. Methods: Multicentre, investigator-initiated, randomised, double-blind, placebo-controlled, parallel-design phase 3b trial in 11 Portuguese rheumatology centres. Patients with PsA along with active dactylitis and naive to MTX and biologic disease-modifying antirheumatic drugs (bDMARDs) were randomly assigned to golimumab or placebo, both in combination with MTX. The primary endpoint was Dactylitis Severity Score (DSS) change from baseline to week 24. Key secondary endpoints included DSS and Leeds Dactylitis Index (LDI) response, and changes from baseline in the LDI and MRI dactylitis score. Analysis was by intention-to-treat for the primary endpoint. Results: Twenty-one patients received golimumab plus MTX and 23 MTX monotherapy for 24 weeks. One patient from each arm discontinued. Patient inclusion was halted at 50% planned recruitment due to a favourable interim analysis. Median baseline DSS was 6 in both arms. By week 24, patients treated with golimumab plus MTX exhibited significantly greater improvements in DSS relative to MTX monotherapy (median change of 5 vs 2 points, respectively; p=0.026). In the golimumab plus MTX arm, significantly higher proportions of patients achieved at least 50% or 70% improvement in DSS and 20%, 50% or 70% improvement in LDI in comparison to MTX monotherapy. Conclusions: The combination of golimumab and MTX as first-line bDMARD therapy is superior to MTX monotherapy for the treatment of PsA dactylitis. Trial registration number: NCT02065713